Characterization of zirconia sulfate catalyst for sustainable aviation fuel from waste cooking oil - Widasgantri, Treisnaning; Widjaja, Tri; Dahnum, Deliana; Altway, Ali; Lamhotmatua, Thasya; Antonius, Kevin (Center of Biomass & Renewable Energy (CBIORE), 2026)
The growing accumulation of waste cooking oil (WCO) in Indonesia presents serious environmental concerns while offering potential as a renewable feedstock for sustainable aviation fuel. This study evaluates the conversion of WCO into bio-jet fuel via pyrolytic catalytic cracking (PCC) using cobalt-dispersed sulfated zirconia (Co/ZrO₂–SO₄, Co/SZ) catalysts under atmospheric pressure. Sulfated zirconia was synthesized hydrothermally and impregnated with 1, 3, and 5 wt% cobalt. Catalyst characterization by FTIR, XRD, BET, and SEM–EDX confirmed successful cobalt dispersion, preservation of the monoclinic ZrO₂ phase, and increasing surface area with higher cobalt loading (83.93 to 111.19 m² g⁻¹). Catalytic performance was tested in a fixed-bed reactor at 400, 430, and 460 °C with a feed-to-catalyst ratio of 100:1. GC–MS analysis revealed that both temperature and cobalt loading significantly influenced selectivity toward the jet fuel fraction (C₁₂–C₁₆). The highest bio-jet fuel selectivity (68.63%) and yield (57.46 wt%) were obtained using 5 wt% Co/SZ at 400°C. At 430 °C, excessive secondary cracking reduced selectivity to 27.78% for 3 wt% Co/SZ, with gasoline-range products reaching 62.70%. Increasing the temperature to 460 °C partially restored jet-range selectivity to 62.67% for 5 wt% Co/SZ due to enhanced isomerization and aromatization reactions. Reusability tests indicated gradual catalyst deactivation caused by coke deposition and loss of acid sites. These results demonstrate that the synergistic interaction between sulfated zirconia acidity and cobalt’s deoxygenation functionality enables efficient WCO conversion into bio-jet fuel, highlighting Co/SZ as a promising catalyst for sustainable aviation fuel production.